PERCEPÇÕES DE GESTORES SOBRE O ATENDIMENTO À MULHERES TRANS VENEZUELANAS EM BOA VISTA E MANAUS - SILVA, Renata Layssa Ferreira da (2025)
INTRODUCTION: The migration phenomenon poses significant challenges to public health, especially in serving vulnerable populations. Brazil, inserted in the context of international migration, has received a large contingent of Venezuelans due to the political and economic crisis in the neighboring country. Among these migrants, trans women face additional obstacles in accessing essential services, which highlights the urgency of inclusive public policies that are sensitive to migration and gender status, especially in a country recognized as one of the most dangerous for trans people. OBJECTIVE: To analyze the perceptions of managers about the care provided to Venezuelan trans women who migrated to Boa Vista (RR) and Manaus (AM). METHOD: This is a qualitative approach, using semi-structured interviews conducted with managers in Boa Vista (RR) and Manaus (AM) by intentional sampling. Data exploration was based on Content Analysis in the Thematic modality and Pierre Bourdieu's theory, which offers a framework for understanding human relations in the social field. RESULTS: The study, divided into three categories of analysis, reveals the perception of sixteen managers about the challenges faced by Venezuelan trans women migrants. In the category dealing with transphobic habitus and symbolic violence, managers report how prejudice and discrimination are perpetuated from their country of origin to Brazil. The category for symbolic and sociocultural capital in mediating access to rights analyzes the power relations that determine the realization or denial of vital resources, such as access to health and housing. Finally, the category of sex work as economic capital highlighted the stigma surrounding this practice as a means of survival. Although advances in care are highlighted, institutional gaps and gaps in the integration of public policies sensitive to gender and nationality persist. CONCLUSION: The managers' perception highlights a criticism of systemic deficiencies, with emphasis on the scarcity of specialized public services. The lack of a robust state structure limits the effectiveness of support initiatives, which depend heavily on non-governmental organizations and international humanitarian aid agencies. The findings highlight opportunities for improvement in building a service network that guarantees dignity to these women for their full integration into Brazilian territory.